2019
DOI: 10.2134/jeq2018.04.0167
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Impact of Cattle Access to Watercourses: A Review

Abstract: The degradation of freshwater resources and loss of freshwater biodiversity by anthropogenic activities, including agriculture, are of major global concern. Together with diffuse pollutants, point sources, such as where cattle have direct access to riparian margins and watercourses, can potentially present significant environmental challenges. These can include impacts on stream morphology, increased sedimentation, nutrient additions, microbial contamination, and impacts on aquatic biota. Mitigation measures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 117 publications
(183 reference statements)
3
58
1
1
Order By: Relevance
“…Similarly, any light limitation to periphyton due to water quality (e.g., high turbidity) may reduce or eliminate undesirable levels of growth 7 . High turbidity is particularly prevalent in dry areas and areas with a high proportion of cropland, intensive grazing or other catchment disturbances like dredging [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, any light limitation to periphyton due to water quality (e.g., high turbidity) may reduce or eliminate undesirable levels of growth 7 . High turbidity is particularly prevalent in dry areas and areas with a high proportion of cropland, intensive grazing or other catchment disturbances like dredging [50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…phosphorus, nitrogen, sediment) involved and the inherent variability in characteristics found between and within catchments (Belsky et al, 1999). Variables such as climate, landscape factors, biophysical characteristics of the stream and land management practices (including stocking rate) all play a role in influencing the impact of cattle access on water parameters, including macroinvertebrates (O'Callaghan et al, 2018). Despite variability in results, measures that prevent cattle access to watercourses are commonly implemented through agri-environment schemes (AESs).…”
Section: Discussionmentioning
confidence: 99%
“…The severity of impact of cattle access on watercourses is influenced by factors such as cattle stocking density, breed, age and condition, e.g. Bond et al (2014) concluded that at appropriate stocking densities, direct nutrient inputs from cattle accessing streams may have only a minor effect on stream water quality (for further reading see O'Callaghan et al, 2018). EU member states must achieve or maintain at least 'good' ecological and chemical status in all waters by 2027 (Water Framework Directive (WFD) 2000/60/EC).…”
Section: Introductionmentioning
confidence: 99%
“…However, since the buffers also enhanced water quality, the authors recommended restructuring the subsidies attained to be increased when multiple ecosystem services were achieved. O'Callaghan et al (2019) showed that for sediment, livestock poaching causes localized bank damage, in turn leading to further erosion, and that direct cattle access to watercourses resuspends bed sediments. They found that riparian fencing has implications for management in supplying alternative watering for cattle (in terms of their funding and maintenance) for animal welfare (removing access to tree shade).…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
“…In turn, this benefits habitat quality and ecosystem services in field (Smart et al, 2006; Ricketts et al, 2008; Dybkjær et al, 2012) and instream (Harrison and Harris, 2002). Although issues of weed transfer and harboring of crop pests from the buffer require management, in their review of the effects of riparian grazing impacts and benefits of access management, O'Callaghan et al (2019) make the important point that catchment‐wide strategies may have a bigger influence on aquatic and riparian ecology than localized riparian management.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%